1998
DOI: 10.1111/j.1558-5646.1998.tb05145.x
|View full text |Cite
|
Sign up to set email alerts
|

DISENTANGLING THE EFFECTS OF MATING PROPENSITY AND MATING CHOICE INDROSOPHILA

Abstract: Abstract.-Incipient sexual isolation between genotypes, lines, or populations of the same species is commonly measured in Drosophila by choice tests. Results of these tests are known to be influenced, in an undetermined manner, by the mating propensity of competitors and by discriminatory factors during courtship. We have approached the problem by measuring male and female propensities in separate, independent tests, and by examining whether these estimates could explain the results of the choice tests. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 32 publications
1
59
0
Order By: Relevance
“…It is known from many studies in Drosophila (Manning 1963;Kessler 1969Singh & Chatterjee 1987;Singh & Sisodia 1999) that variation in parameters of mating propensity may appear on the level of populations and strains. Recently, it was clearly shown that di¡erences in mating propensity can lead to non-random mating in mate choice situations and be erroneously interpreted as discrimination (Casares et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known from many studies in Drosophila (Manning 1963;Kessler 1969Singh & Chatterjee 1987;Singh & Sisodia 1999) that variation in parameters of mating propensity may appear on the level of populations and strains. Recently, it was clearly shown that di¡erences in mating propensity can lead to non-random mating in mate choice situations and be erroneously interpreted as discrimination (Casares et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, male mating propensity is measured in nonchoice tests as time elapsed from introduction of mating partners into the mating chamber until copulation (Casares et al 1998) or the number of females mated (Ringo et al 1986). These de¢nitions are probably not absolutely correct for all cases.…”
Section: (A) Sexual Behaviour (I) Mating Propensitymentioning
confidence: 99%
See 1 more Smart Citation
“…The most common of these is the Malogolowkin-Cohen index, which calculates the number of homogamic minus heterogamic matings and divides it by the total number of matings, giving positive values in the case of an excess of homogamic matings, and negative values in the opposite case (Malogolowkinthat can give rise to an erroneous interpretation of the obtained data. Casares et al (1998) have shown that if the two types of males and females differ in their mating propensities, and the number of matings occuring in the tests are close to 100% of all possible matings, then the choice conditions are not maintained and there is a high risk of obtaining significant results that do not correspond to true choice and falsely suggest assortative mating. In other words, mating propensity differences between the studied genotypes can produce significant departures from random mating between different types of flies that could then be erroneously interpreted as evidence of incipient sexual isolation.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible answer emerges from the design and data handling of the multiplechoice mating tests. As discussed above, Casares et al (1998) have demonstrated that mating propensity differences can give rise to deviations from random mating and false positive isolation measures. If one of the two competing types has greater male and female mating propensity than the other type, then homogamic matings will exceed heterogamic ones and the isolation index will be positive.…”
Section: Introductionmentioning
confidence: 99%